Atribut Destinasi Pariwisata dan Kualitas Pelayanan Mempengaruhi Niat Wisatawan Berkunjung Kembali di Pantai Melasti, Desa Ungasan, Kabupaten Badung - Made Riki Ponga Kusyanda; Made Antara; I Gusti Ayu Oka Suryawardani (JURNAL MASTER PARIWISATA, 2020)
The urgency of this research was the utilization of Melasti Beach's trough a professional management operational, it can provide economic benefits for Ungasan Village, one of the point is creating guest satisfaction and re-visit intention continuesly. The goals of these study was (1) Analyze the effect of tourism destination attributes toward guest re-visit intention of tourists on Melasti Beach trough the guest satisfaction as the intervening , (2) to analyze the effect of service quality toward re-visit intention into Melasti Beach trough the guest satisfaction as the intervening (3) to anlyze the effect of guest satisfaction toward revisit intention . The sample of this study was 100 tourists consisting for domestic and foreign tourist. Using incidental sampling method to reach the respondent. Primary data is obtained through questionnaires. The data analysis method used is a quantitative approach and using structural equation models- partial least square or Smartpls version 3.0 and also described by descriptively to conduct the research. The finding of thes study is almost all of the hypothesis is accepted, except hypothesis no. 4 were rejected due to there were no significant relation between service quality toward tourist re-visit intention, and hypothesis no. 6 were there was no significant influence on tourism destination attribute toward tourist intention re-visit intention through tourist satisfaction. The advice of these research generally advice to keep the tourism destination attribute as the determinant factor, in how to effect the revisit intention by the guest in the near future. Keywords: Tourism destination attributes, service quality, tourist satisfaction, tourist re-visit intention.